The construct of cognition in language teacher education and development - Bartels, Nathaniel; Justus Liebig University Giessen (My University, 2006)
Chapter 1: Central issues in the field of second language teacher education (SLTE) rest on conceptions of human cognition: what knowledge is, how it is acquired, and how it is used. However, human cognition is not a focus of the academic disciplines which usually are in charge of SLTE programs; research and theory on the nature of human cognition is usually not included in debates on SLTE. The purpose of this dissertation is to use a wide range of work on human cognition to address and evaluate fundamental issues in SLTE. Chapter 2: This chapter examines the professional conceptions of SLTE that have been proposed throughout the years in order to understand the conceptions of cognition that they assume. There were four main issues found: (1) the assumption that explicit knowledge guides teachers practice, (2) that general knowledge (i.e., knowledge which academics produce) is more useful than specific, context-bound information, (3) that teachers practice is guided by general principles and if these principles are changed, teachers practice will change, and (4) if teachers recognize problems in their practice, they will be able to solve them. Chapter 3: Studies show that knowledge transfer from SLTE programs to L2 teaching is very difficult and problematic. Language teachers find it very difficult to use academic information or theoretical principles in their practice. Humans in general are not very good at taking knowledge gained from one activity and using it in another and will even resist knowledge which contradicts knowledge they already possess. Chapter 4: Human cognition is not unlimited; there are some important constraints on the kinds of cognitive operations we can engage in. A central constraint is the limited amount of information that can be explicitly processed at any one time in working memory; because of this, knowledge which needs to be explicitly processed, such as declarative knowledge, is very inefficient. On the other hand, implicit knowledge, which is largely processed outside of working memory, is cognitively efficient. Studies of experts have shown that they are able to perform better than others because they use their implicit knowledge to recognize important cues as well as actions which have good chances of achieving their objectives in that specific situation. Chapter 5: SLTE programs typically focus on general knowledge about language, language learning and language teaching. However, in this chapter a wide range of evidence is presented which indicates that teachers need and use knowledge specific to the practice of teaching, not general knowledge from academic fields related to language. Chapter 6: How teachers knowledge is organized is just as important as the amount of knowledge a teacher possesses. A well organized knowledge base helps teachers match student cues or their instructional agenda with options for action automatically without demanding much of their scarce explicit processing capacity. However, teachers knowledge organization is different from the organization of explicit, academic knowledge. Instead of general conceptions which account for all relevant factors, teachers rely on a dynamic network of practice-specific knowledge, which allows teachers to continually construct interpretations of student behavior, instructional goals and other classroom issues as activities unfold in the classroom. Chapter 7: Research indicates that for teachers to acquire the kind of knowledge they need within SLTE programs, they need to have explicit cognitive processing capacity available for learning during SLTE activities. If teachers need to pay attention to too many factors, they will suffer from cognitive overload and will not be able to learn much. Therefore, one of the central responsibilities of SLTE teachers is to manage the cognitive load of their students. Chapter 8: It is possible, however, that, over time, teachers use explicit, academic knowledge to generate implicit, specific knowledge organized around L2 teaching. This chapter presents the results of three empirical studies undertaken to test this hypothesis using three separate tasks selected because they are the prototypical tasks used to investigate expertise and knowledge organization: a memory task, a sorting task, and a performance task. The results of these studies suggest that even over a lengthy period of time these teachers (n=19) had not used explicit knowledge about language to create deliberate practice activities which result in implicit, specific, and dynamically-organized practitioner knowledge. Chapter 9: This chapter begins by evaluating the hypotheses underlying traditional conceptions of SLTE which were presented in the second chapter. The evidence does not support these hypotheses, but does support the position of others who have argued that (a) SLTE needs to focus on the activity of teaching and the contexts of teaching and (b) that developing expertise requires reinvestment of cognitive resources into deliberate practice. A model of teacher knowledge use and acquisition is presented and discussed.

In den letzten 15 Jahren hat es einen großen Forschungs- und Interessenszuwachs zur Kognition und Ausbildung von Zweitsprachenlehrern gegeben. Kapitel 1 und 2 stellen die wichtigsten Fragen oder Hypothesen dieses Konzepts der menschlichen Kognition vor. Kapitel 3: Untersuchungen haben gezeigt, dass die meisten Lehrer nicht in der Lage sind, in ihrer Unterrichtspraxis erfolgreich Wissen zu nutzen, das sie in ihrer Ausbildung erworben haben. Ein Teil des Problems scheint zu sein, dass Lehrer nicht lernen, ihr Wissen unter den Einschränkungen zu nutzen, die es in vielen Lehrzusammenhängen gibt, wie z.B. Zeitmangel. Kapitel 4: Eine der grundlegendsten Einschränkungen des menschlichen Lernens ist das Arbeitsgedächtnis, das nur wenige Dinge gleichzeitig verarbeiten kann. Explizites Wissen wird hauptsächlich im Arbeitsgedächtnis verarbeitet, daher erfordert das Arbeiten mit explizitem Wissen meistens viel mehr Verarbeitungszeit als vorhanden ist. Wegen dieser Einschränkung des Arbeitsgedächtnisses wird für das Erreichen von Expertise ein Wissen benötigt, das so wenig explizite Verarbeitungskapazitäten wie möglich in Anspruch nimmt: implizites Wissen. Kapitel 5: Untersuchungen zeigen, dass Lehrer (und Menschen generell) allgemeines Wissen oder allgemeine Prinzipien nicht besonders gut anwenden können. Statt dessen deuten immer mehr Forschung darauf hin, dass sich Lehrer beim Unterrichten auf spezifisches, detailliertes, kontextgebundenes Wissen stützen. Kapitel 6: Das Maß, zu welchem das Lehrerwissen um die Unterrichtsaktivitäten herum organisiert ist, ist auch von Wichtigkeit. Wenn Wissen um den Unterricht herum organisiert ist, kann die Beobachtung eines Lehrers angemessene Reaktionen auch ohne explizites Wissen auslösen. Ohne diese Verbindungen würden Lehrer ihre Reaktionen explizit ausarbeiten müssen, was wiederum knappe explizite Verarbeitungskapazitäten in Anspruch nehmen würd. Kapitel 7: Wenn die Ausbildung von Zweitsprachenlehrern darauf abzielt, Lehrern eine reiche Basis an unterrichtsspezifischem, verbundem, implizitem Wissen zu vermitteln, muss sie darauf achten, wie sie die Lernerfahrungen in der Ausbildung strukturiert. Kapitel 8: Es ist aber möglich, dass Lehrer explizites, akademisches Wissen nutzen, um implizites, spezifisches Wissen rund um den Zweitsprachenunterricht zu entwickeln. Zur Untersuchung dieser Fragen wurde das Ausmaß, in wieweit erfahrene Lehrer (n=19) gut organisiertes, implizites Wissen nachweisen konnten, überprüft. Drei getrennte Aufgaben wurden genutzt, um das Wissen über die Schülersprache zu testen: eine Gedächtnisaufgabe, eine Sortieraufgabe und eine Performanzaufgabe. Die von den Lehrern produzierten Daten, wurden mit den Ergebnissen von Linguisten (n=19) und einer Kontrollgruppe (n=18) aus gleichen Aufgabenstellungen verglichen. Keine Aufgabe zeigte signifikante Unterschiede zwischen den Lehrern und den anderen Teilnehmern. Die Ergebnisse können als stichhaltiger Beweis dafür gelten, dass diese Zweitsprachenlehrer ihre wissenschaftliche Kenntnisse nicht angewendet haben, um domänenspezifisches, implizites, Wissen zu entwickeln. Kapitel 9: Die in dieser Arbeit präsentierten Untersuchungen zeigen, dass ein neues Kognitionskonzept notwendig ist. Ein Arbeitsmodell mit dem Schwerpunkt Lehrerkognition und Lehrerlernen wird präsentiert in dem das implizite Wissen steuert eines Lehrers die Aktion. Die lokalen Faktoren, die für die Aktion des Lehrers wichtig sind, stimulieren das implizite Wissen des Lehrers. Dies aktiviert die Erklärungs- und Prozessschemata des Lehrers sowie sein Wissen über spezifische Aktivitäten und pädagogische Begriffe, Unterrichtsroutinen und andere Arten impliziten Wissens bis eine Wissensansammlung eine Erklärung der Situation und/oder eine mögliche Handlungsfolge bildet. Explizites Wissen kann dazu verwandt werden, die Ergebnisse der impliziten Kognition zu evaluieren aber es leitet die Aktion nicht an. Ist das implizite Wissen der Lehrerin gut organisiert, ist die Zusammenstellung einer Erklärungs- und Aktionsfolge leichter. Entsprechend dem hier präsentierten Konzept der menschlichen Kognition, muss die Ausbildung von Zweitsprachenlehrer ihre Studenten als Lehrer ausbilden nicht als Wissenschaftler. Lehrer müssen lernen, wie erfahrene Lehrer zu denken und wahrzunehmen; sich in den Aktivitäten üben, die das Lehren ausmachen (z.B. Stundenplanung, das Ausführen und interaktive Verändern von Aktivitäten, die Reaktion auf Schülerarbeiten, eigene Verbesserungsarbeit als Lehrer etc.), und spezifische Lehraktivitäten, Kontexte, Schüler und deren Einfluss auf spezifische Unterrichtssituationen kennen lernen. All dies ist eine Herausforderung für Dozenten der Zweitsprachenlehrerausbildung, da sie meistens nicht dafür ausgebildet wurden und ihnen daher das Wissen und die Fähigkeiten dazu fehlen könnten. Vielleicht können die hier gegebenen Informationen den Dozenten jedoch als Grundlage dienen, bewusste Übungen zu entwickeln und auszuführen, die wiederum zur Veränderung ihrer eigenen impliziten, spezifischen und dynamisch verbundenem Wissensgrundlage für die Ausbildung von Zweitsprachenlehrern führen.
Das Konzept über die Kognition in der Zweitsprachenlehrerausbildung
Keywords: Lehrerkognition; Lehrerwissen; Lehrerausbildung; Angewandte Linguistik; Teacher Cognition; Teacher Knowledge; Teacher Education; Applied Linguistics; ddc:400